2019
DOI: 10.1093/mnras/stz022
|View full text |Cite
|
Sign up to set email alerts
|

The Santiago–Harvard–Edinburgh–Durham void comparison II: unveiling the Vainshtein screening using weak lensing

Abstract: We study cosmic voids in the normal-branch Dvali-Gabadadze-Porrati (nDGP) braneworld models, which are representative of a class of modified gravity theories where deviations from General Relativity are usually hidden by the Vainshtein screening in high-density environments. This screening is less efficient away from these environments, which makes voids ideally suited for testing this class of models. We use N-body simulations of Λ-cold dark matter (ΛCDM) and nGDP universes, where dark matter haloes are popul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 82 publications
1
65
1
Order By: Relevance
“…Colberg et al (2008) compared a total of 13 void finders identifying voids from the Millennium simulation. More recent studies by Cautun et al (2018) and Paillas et al (2019) compared various void definitions, focussing on their potential to differentiate between either Chameleon-, or Vainshteintype modified gravity and ΛCDM via weak lensing. But not only discrete tracer distributions have been considered for this purpose, as demonstrated by Davies et al (2018Davies et al ( , 2019 using weak-lensing maps and by Krolewski et al (2018) using the Lyman-α forest to identify voids.…”
Section: Take Down Policymentioning
confidence: 99%
“…Colberg et al (2008) compared a total of 13 void finders identifying voids from the Millennium simulation. More recent studies by Cautun et al (2018) and Paillas et al (2019) compared various void definitions, focussing on their potential to differentiate between either Chameleon-, or Vainshteintype modified gravity and ΛCDM via weak lensing. But not only discrete tracer distributions have been considered for this purpose, as demonstrated by Davies et al (2018Davies et al ( , 2019 using weak-lensing maps and by Krolewski et al (2018) using the Lyman-α forest to identify voids.…”
Section: Take Down Policymentioning
confidence: 99%
“…(e.g., Falck et al 2018;Paillas et al 2019). Models which feature Vainshtein screening have also been tested by, for example, comparing weak lensing data with SZ and X-ray cluster observations (Terukina et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sánchez et al (2017) used DES redMaGiC galaxies to identify voids and found the stacked lensing signal around them to be negative at a 4σ level (also see Melchior et al 2014;Clampitt & Jain 2015;Gruen et al 2016). The lensing profile around underdense regions has also been a topic of interest for modified gravity, as dark energy is more prominent in void regions (Barreira et al 2015(Barreira et al , 2017Baker et al 2018;Paillas et al 2019). Void lensing can be more complicated than cluster lensing, as voids may have irregular shapes and the lensing signal depends on the void identification scheme.…”
mentioning
confidence: 99%